Arboreal Extension of an Order - Pimenta, Adriana; Klein, Sulamita (Cadernos do IME - Série Informática, 2022)
This article describes the contribution of Adriana Pimenta, Jayme Szwarcfiter, Michel Habib and Sulamita Klein on arboreal extensions of partial orders, started in 2008. The quantity to be determined is about the minimum number of arboreal jumps of a partial order.